2014
DOI: 10.1016/j.matbio.2014.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomics at different depths in human articular cartilage reveals unique patterns of protein distribution

Abstract: The articular cartilage of synovial joints ensures friction-free mobility and attenuates mechanical impact on the joint during movement. These functions are mediated by the complex network of extracellular molecules characteristic for articular cartilage. Zonal differences in the extracellular matrix (ECM) are well recognized. However, knowledge about the precise molecular composition in the different zones remains limited. In the present study, we investigated the distribution of ECM molecules along the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 45 publications
3
51
0
Order By: Relevance
“…Cleavage of aggrecan by HTRA1 was strongly enhanced by HTRA1 agonists such as CPII, a C-terminal hexapeptide derived from the C-propeptide of procollagen IIα1 [57]. HTRA1 is preferentially localized in the deep layer of cartilage [34] and increased during chondrocyte differentiation of MSCs [26], and by TGF-β1 stimulation [24]. HTRA1 is reduced 4-fold in OA vs normal chondrocytes [35], with no difference detected between OA and normal decellularized cartilage [37].…”
Section: Proteolytic Enzymes and Their Regulatorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Cleavage of aggrecan by HTRA1 was strongly enhanced by HTRA1 agonists such as CPII, a C-terminal hexapeptide derived from the C-propeptide of procollagen IIα1 [57]. HTRA1 is preferentially localized in the deep layer of cartilage [34] and increased during chondrocyte differentiation of MSCs [26], and by TGF-β1 stimulation [24]. HTRA1 is reduced 4-fold in OA vs normal chondrocytes [35], with no difference detected between OA and normal decellularized cartilage [37].…”
Section: Proteolytic Enzymes and Their Regulatorsmentioning
confidence: 99%
“…In this part of the review, we focused on proteins identified either directly in the secretome of cartilage explants [12][13][14][15][16][17][18][19][20] or chondrocytes cultures [18,[21][22][23][24][25][26][27][28][29][30][31]), both of which are listed in Table 1. We further complete this list with proteins recently identified by proteomic analysis performed directly on fresh chondrocytes or cartilage tissue [32][33][34][35][36] (sometimes de-cellularized [37]) whereby different locations in the joint were compared, or healthy joint tissues were compared with 6 OA tissues. The characteristics of all these studies are summarized in Table 2.…”
Section: Chondrocyte Secretomementioning
confidence: 99%
See 3 more Smart Citations